PENGARUH PENAMBAHAN BIOAKTIVATOR EM-4 TERHADAP PRODUKSI BIOGAS DARI LIMBAH CAIR INDUSTRI TAHU - Jamiluddin Ahmad Muzakki (Relawan Jurnal Indonesia, 2021)
Tofu industrial waste is generally divided into two forms of waste, namely solid waste and liquid waste. The liquid waste of the tofu industry contains organic material that can be decomposed anaerobically into methane gas (CH4), other gases, and water which is commonly called biogas. One of the potential biocatalysts as a source of microorganisms in biogas production is Effective Microorganisms 4 (EM-4). This research was conducted by adding EM-4 with a concentration of 0.5%; 1%; and without EM-4 into 15 liters of tofu liquid waste in the digester for fermentation for 7 days. Observation of the pressure on the manometer seen from the difference in the height of the liquid manometer U and the combustion process was carried out on the 7th day (constant pressure). The maximum pressure of biogas for 7 days at 1% EM4 of 927,864 kg/m.s2 produces a blue flame, has an unpleasant odor, does not cause smoke with a fire height of 12,602 mm. So it can be concluded that the greater concentration of EM-4 used, the greater the pressure of biogas and fire